2008
DOI: 10.1080/10887150801967704
|View full text |Cite
|
Sign up to set email alerts
|

Six critical ingredients in creating an effective workplace.

Abstract: Using a nationally representative sample of data collected from waged and salaried employees in the United States (n = 2810) by the 2002 National Study of the Changing Workforce (NSCW), we evaluate workplace flexibility as another critical ingredient in creating an effective workplace. The study examined the bivariate relationships between six factors of workplace effectiveness and three job outcomes (job engagement, job satisfaction, employee retention) and one employee outcome (mental health). It also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…These results suggest that employees who work in an environment o f empowerment and trust, experience their m anagers as supportive o f them and their careers, who receive regular feedback and recognition, and who understands how their goals fit in with the overall strategy o f the organisation, report higher levels o f energy and mental resilience at work, a stronger involvement in their work, a sense of significance and pride, and are also more likely to concen trate fully on and be engrossed in their work. The results o f the study are aligned with those obtained in previous research that found positive relationships between the performance management activities of employee develop ment (Jacob et al, 2008;Mone & London, 2010;Schaufeli & Salanova, 2007), feedback and recognition (Mone & London, 2010;Schaufeli & Salanova, 2007), goal setting (Gruman & Saks, 2011;Macey et al, 2009;Mone & London, 2010) coaching (Macey et al, 2009;Mone & London, 2010) and engagement.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that employees who work in an environment o f empowerment and trust, experience their m anagers as supportive o f them and their careers, who receive regular feedback and recognition, and who understands how their goals fit in with the overall strategy o f the organisation, report higher levels o f energy and mental resilience at work, a stronger involvement in their work, a sense of significance and pride, and are also more likely to concen trate fully on and be engrossed in their work. The results o f the study are aligned with those obtained in previous research that found positive relationships between the performance management activities of employee develop ment (Jacob et al, 2008;Mone & London, 2010;Schaufeli & Salanova, 2007), feedback and recognition (Mone & London, 2010;Schaufeli & Salanova, 2007), goal setting (Gruman & Saks, 2011;Macey et al, 2009;Mone & London, 2010) coaching (Macey et al, 2009;Mone & London, 2010) and engagement.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with other scholars' findings (Galinsky et al, 2002;Jacob et al, 2008;Rogier & Padgett, 2004;Sullivan & Mainiero, 2007): Organizations clearly benefit by offering FWAs that enable women to act as career self-agents. From highest to lowest return, organizations benefit by fostering a workforce that is more "willing to go the extra mile," translating into greater productivity, and employees who are more "loyal in remaining at the organization," translating into higher retention.…”
Section: Discussionsupporting
confidence: 95%
“…AT&T garnered $150 million in extra hours of productive work from telecommuting workers (Bednarz, 2005). Jacob, Bond, Galinsky, and Hill (2008) considered the benefits of improved job engagement and mental health, and decreased health care costs, suggesting that organizations "consider new options for flexibility not as 'perks' to accommodate employee needs, but as strategic management tools that can improve business performance" (p. 158). To capture those benefits, Sullivan and Mainiero (2007) provided an extensive list of policies for organizations to implement.…”
Section: Literature Review and Research Questionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, when workers experience difficulties in managing their lives effectively because of inflexible work arrangements, work suffers and the risk for turnover increases (Jacob, Bond, Galinsky, & Hill, 2008). Thus, in offering flexible work options to their workers, employers indirectly achieve their organizational goals .…”
Section: Benefits Of Workplace Flexibilitymentioning
confidence: 93%